Communicating User Experience: Applying Local Strategies Research to Digital Media Design - Milburn, Trudy (Lexington Books, 2015)
Communicating User Experience: Applying Local Strategies Researchto Digital Media Design examines how Local Strategies Research (LSR) helps investigate user experiences with digital media. This edited collection uses case studies to examine the way we communicate in the digital age whether between individuals and digital interfaces (such those installed in cars), dyads via mobile phones and online interfaces, or members of a group through a video conference. Milburn and her contributors consider the cultural norms that both inform and are used during interaction to provide a useful methodology that shifts design (particularly HCI) research from a focus on emotional, subjective user experiences to the everyday practices involved in interacting with one another in and through digital devices and interfaces. Communicating User Experience will be a valuable resource for designers and scholars of communication and new media.